Development Of Three Dimensional Simulation On Colon Cancer - Rahim, Sarni Suhaila; Parumo, Shahril; Pedrik, Cybill (World Academy of Research in Science and Engineering (WARSE), 2020)
Colon, or colorectal cancer is a cancer that starts in the large intestine, also called colon, or happens in the rectum, which is the end of the colon. This simulation on colon cancer will show the user in 3D animation all about colon cancer. In addition, this simulation will explain about colon cancer and how cancer cell developed in the colon. Nowadays, the style of channeling the information makes it boring to public. Moreover, the 2D simulation gives less impact to the audience. An effective delivery of knowledge of colon cancer is important as colon cancer is the third commonest cancer worldwide. The main objective of this project is to develop a simulation that explains about colon cancer. The project also aims to implement 3D simulation in explaining in more detail about the colon cancer. Besides, this project aims to evaluate the effectiveness of 3D simulation of the colon cancer. There are three modules presented in this simulation, which are Introduction to Colon Cancer, Simulation on How the Colon Cancer Happens and Effects if Colon Fails to Function Properly. It is envisaged that this project will contribute in delivering a more effective understanding about colon cancer by using 3D animation. It is also hoped that this 3D simulation is useful for public by providing the information on colon cancer.